Conflict – Crisis Hierarchy in English News Discourse: Cognitive Rhetorical Perspective - Potapenko, Serhiy I.; Shcherbak, Olena M. (Research in Language, 2020)
The paper argues that in English on-line news the meanings of the conflict and crisis terms serve as reference points for the construction of a confrontation hierarchy. It is based on the interaction of the relations of force, serving as primes for meaning formation, with three levels of discourse prominence meant to attract, focus and keep the addressee’s attention in headings, headlines and throughout the text respectively. It is found that news stories arrange the units of conflict – crisis hierarchy according to three patterns: zoom-in, offering a detailed textual representation of confrontation with support of the argumentation sections of evidence, explanation or commentary; zoom-out, generalizing on the forces, underlying confrontation construction; multiperspectivation, aimed at a multifaceted representation of conflict – crisis hierarchy.